Implications of Vitamin D Status for Children's Bone Health: A Data Mining Analyses of Observational Studies - Mariana Leonel Martins; Beatriz Fernandes Arrepia; Lucas Jural; José Vicente-Gomila; Daniele Masterson; Lucianne Cople Maia; Maria Augusta Visconti; Andréa Fonseca-Gonçalves (Association of Support to Oral Health Research (APESB), 2024)
Objective: To investigate associations/correlations between bone alterations and vitamin D status in children through data mining analyses based on observational studies. Material and Methods: Searches in PubMed, Scopus, Web of Science, and Embase databases were performed to recover studies, published until October 2022, with healthy children, which investigated the vitamin D status, related or not to undesirable bone alterations linked to bone quality (bone mineral density and bone mineral content), fracture or anthropometry. Country, study design, area of expertise (medicine, nutrition, dentistry, others), bone outcome, 25-hydroxyvitamin D data (serum or intake levels), the exams for bone diagnosis, and the results were analyzed in the VantagePointTM software. Results: Of 20,583 studies, 27 were included. The USA (n=9; 33.3%) had the highest number of publications. Cross-sectional (n=11; 40.7%), case-control (n=9; 33.3%), and cohort studies (n=7; 25.9%) contemplated the medicine and nutritional areas without any study in dentistry. Studies about bone quality (n=21; 77.8%), analyzed through dual-energy X-ray absorptiometry (DXA; n=14; 51.8%), with association (n=16; 59.2%) between the low serum levels of 25-hydroxyvitamin D and undesirable bone alterations (n=14; 51.8%) were the most prevalent. Conclusion: Most studies were conducted in the medical area and showed an association between low bone quality and low levels of 25-hydroxyvitamin D, verified through DXA.